The impact of convergence insufficiency on selective visual attention among university students - Mohammed M. Alnawmasi (PLoS ONE, 2025)
Convergence insufficiency (CI) is a common binocular vision disorder that impairs near vision-related tasks and is associated with symptoms such as eye strain, headaches, and reading difficulties. This study examined the effect of CI on selective visual attention by comparing performance on a modified visual search task between patients with CI and visually normal controls. A total of 42 male university students participated, including 20 patients diagnosed with CI and 22 age-matched controls. Participants completed a computerized visual search task involving different levels of target-distractor similarity and number of distractors. Accuracy (percent correct) and reaction time (RT) were recorded across task conditions. Reaction time was significantly slower in the CI group across all task conditions (mean RT: 1.21 ± 0.15 s) compared to controls (mean RT: 0.97 ± 0.12 s; main effect of group: F(1,160) = 38.2, p < 0.0001), while accuracy did not significantly differ between groups (CI: 86.3% ± 5.7; controls: 87.1% ± 6.1; F(1,160) = 0.002, p = 0.97). Task difficulty significantly influenced both accuracy (F(3,160) = 37.9, p < 0.001) and reaction time (F(3,160) = 5.1, p = 0.002), but no interaction effects were observed. Moreover, linear regression revealed a significant positive correlation between CISS scores and reaction time within the CI group (R² = 0.30, p = 0.01), indicating that higher symptom severity was associated with greater cognitive processing delay. In conclusion, CI has a negative impact on processing speed but not on accuracy during attentionally demanding tasks. These findings have implications for academic performance and highlight the importance of considering visual processing speed in clinical assessments and interventions for CI.